2010
DOI: 10.1063/1.3455716
|View full text |Cite
|
Sign up to set email alerts
|

Structural transitions and dipole moment of water clusters (H2O)n=4–100

Abstract: The properties of water clusters (H2O)n over a broad range of sizes (n=4–100) were studied by microcanonical parallel tempering Monte Carlo and replica exchange molecular dynamics simulations at temperatures between 20 and 300 K, with special emphasis in the understanding of relation between the structural transitions and dipole behavior. The effect of the water interaction potential was analyzed using six nonpolarizable models, but more extensive calculations were performed using the TIP4P-ice water model. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 59 publications
4
28
2
Order By: Relevance
“…In aqueous ClH and PPN the decrease in T changes the equilibrium between free C153 molecules concentration and C153+H 2 O complexes in favor of the former ones. This is related to the fact water forms clusters of the size increasing with decreasing T [12,25], thus reducing the concentration of water molecules accessible for C153 to form complexes. The difference in M e→g and k nr must be small for C153 and its complex with water and we observe an average result as the decay time.…”
Section: Discussionmentioning
confidence: 99%
“…In aqueous ClH and PPN the decrease in T changes the equilibrium between free C153 molecules concentration and C153+H 2 O complexes in favor of the former ones. This is related to the fact water forms clusters of the size increasing with decreasing T [12,25], thus reducing the concentration of water molecules accessible for C153 to form complexes. The difference in M e→g and k nr must be small for C153 and its complex with water and we observe an average result as the decay time.…”
Section: Discussionmentioning
confidence: 99%
“…43 Considering their hydrogen bond (HB) connectivity pattern, both isomers present four water molecules acting as double-donor-single acceptors (DDSA) while the other four act as single-donor-double-acceptors (SDDA) and exhibit dangling hydrogens (H dng ). From a thermodynamic perspective, computer simulations have already revealed that these aggregates undergo solid-liquid phase transitions in a thermal range spanning, roughly, the 150 K-200 K interval, 31,34,[44][45][46] and that the explicit introduction of quantum nuclear fluctuations shifts the predicted melting temperature down by about 10-20 K. 47,48 Typically, quantum simulation studies for water have been carried out using potential energy surfaces borrowed from classical force fields for the bulk. As a possible improvement, Manolopoulos and co-workers 49 introduced the flexible q-TIP4P/F model, specifically tailored to avoid implicit quantum effects and be implemented in path-integral simulations of water.…”
Section: Introductionmentioning
confidence: 99%
“…In the bottom panel of Fig. 2 we compare the heat capacity computed for (DDW) 30 using RE 76 and PINS54 simulations with the results expected from the deterministic computation in Eq. (7).…”
Section: Infinite Swapping and Partial Infinite Swapping In R Nmentioning
confidence: 99%
“…where dX = dx 1 dx 2 · · · dx N , P n is the permutation operator, and idnx(n, k) is the pointer to all the permutations in the coordinate-temperature list associated with temperature k. 24 The symbol x i is used to no-development of INS and PINS 24 is particularly timely, given our own interests in simulating molecular clusters, [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] and the difficulties we have encountered in the process. Molecular clusters seem to have a much richer set of rare-event like thermodynamic behaviors compared to an atomic cluster of equivalent size.…”
Section: Introductionmentioning
confidence: 99%